RANCANG BANGUN SISTEM PENGENDALIAN SPAREPART PADA SECTION TECHNICAL 4 DI PT.JMS BATAM - Simanjuntak, Fery; Sirait, Ganda (LPPM Universitas Putera Batam, 2023)
This study discusses the problem of processing spare parts data that is not in accordance with the actual conditions that occur in the production environment of PT JMS Batam. The spare parts recording system is still carried out with a manual recording method that requires each employee to write by hand. Various spare parts name writing techniques cause a non-standard bookkeeping system and confuse admins in recapitulation of bookkeeping. The incompatibility of the recapitulation results with the actual total number of existing spare parts creates a domino effect causing the process of replacing spare parts in various activities of the technical-4 department to be not optimal. By using a database-integrated application, each spare part that will be used first is registered by scanning the barcode owned by each spare part. From the results of the trial by changing the manual recording method to the computerized recording method, it was concluded that the computerized recording system has better performance because it is able to identify deviations of 29% compared to the manual recording system.